2009
DOI: 10.1074/jbc.m901833200
|View full text |Cite
|
Sign up to set email alerts
|

Gene-specific Transcriptional Activation Mediated by the p150 Subunit of the Chromatin Assembly Factor 1

Abstract: Chromatin assembly factor 1 contains three subunits, p150, p60, and p48. It is essential for coupling nucleosome assembly to newly synthesized DNA. Whether chromatin assembly factor 1 subunits have functions beyond escorting histones, which depends on the complex formation of p150 and p60, has been an issue of great interest. This study reveals a novel role of p150, but not p60, in gene-specific transcriptional activation. We found that p150 transcriptionally activated an essential viral promoter, the major im… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
11
0

Year Published

2010
2010
2019
2019

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 11 publications
(11 citation statements)
references
References 32 publications
0
11
0
Order By: Relevance
“…We show that (I) HCMV infection upregulates the protein levels of p150 and p60 of CAF1, as well as PCNA and (II) HCMV IE2 binds to p150 and through this interaction locates the CAF1 complex, possibly with histones, to centers of viral genome synthesis to promote HCMV DNA replication. In addition, we unexpectedly found p150, independently of p60, binds to and activates the HCMV major immediate-early promoter that drives IE2 synthesis [54]. Based on all these, it is hypothesized that an IE2-CAF1 autoregulation loop might facilitate HCMV viral DNA replication.…”
Section: Discussionmentioning
confidence: 96%
“…We show that (I) HCMV infection upregulates the protein levels of p150 and p60 of CAF1, as well as PCNA and (II) HCMV IE2 binds to p150 and through this interaction locates the CAF1 complex, possibly with histones, to centers of viral genome synthesis to promote HCMV DNA replication. In addition, we unexpectedly found p150, independently of p60, binds to and activates the HCMV major immediate-early promoter that drives IE2 synthesis [54]. Based on all these, it is hypothesized that an IE2-CAF1 autoregulation loop might facilitate HCMV viral DNA replication.…”
Section: Discussionmentioning
confidence: 96%
“…Mammalian CAF-1 sustains somatic cell types 38 and epigenetic memory by interacting with heterochromatin protein 1α, a histone H3 methyltransferase and KRAB-ZFP-associated protein 1; this complex is also associated with sub-nuclear foci 39 . Human CAF-1 can also activate transcription independent of its histone deposition function 40 and the conserved CAF-1 subunit-associated dREAM complex plays a role in specifying and maintaining olfactory receptor gene expression in Drosophila 41 . Thus, in addition to housekeeping roles in chromatin assembly, several lines of evidence suggest an evolutionary conserved role for CAF-1 in sustaining site-specific molecular memories of epigenetic states.…”
Section: Discussionmentioning
confidence: 99%
“…RNAi experiments also demonstrated that several H3‐H4‐specific histone chaperones behave as positive acting factors of the herpesvirus productive cycle: HIRA (which presumably mediates H3.3 incorporation into parental HSV‐1 chromosomes; see previous text) and ASF1B facilitate HSV‐1 lytic replication , whereas chromatin assembly factor 1 (CAF1) promotes HCMV replication by assisting in viral IE gene activation . On the other hand, the H2A‐H2B‐specific histone chaperones template‐activating factor I (TAF‐I) and nucleophosmin 1 (NPM1) seem to negatively regulate HSV‐1 productive infection or KSHV reactivation from latency , respectively (Table ).…”
Section: Targeting Of Herpesvirus Chromatinmentioning
confidence: 99%